(untitled) (Biological Sciences - PJSIR, 2022)
Lemongrass (Cymobopogon citratus) is used as a biocontrol agent to suppress the root rotting fungi and ultimately enhance the growth of brinjal (Solanum melongena) plant. During in vitro experiment n-hexane, chloroform and methanol i.e. extracts at different concentrations 10 mL, 20 mL, 30 mL and 50 mL of lemongrass were checked against different fungi like, Rhizoctonia solani, Fusarium solani, F. oxysporum and Macrophomina phaseolina. Application of n-hexane at 50 mL showed highly significant inhibitory zone against all test fungi, while during field experiment the sharp increase in root and shoot length 5% w/v mixture of lemongrass powder and it was applied in Brinjal field. M. phaseolina along with other root rotting fungi like, R. solani, F. solani and F. oxysporum.